Biosimilars for psoriasis: preclinical analytical assessment to determine similarity. (30th December 2015) - Blauvelt, A.; Cohen, A.D.; Puig, L.; Vender, R.; van der Walt, J.; Wu, J.J.
Summary: Biosimilars, sometimes called 'generic biologics', are no longer a vision for the future but a present‐day reality. Drug manufacturers and regulatory authorities are charged with ensuring that these products are safe and effective. Because biologically produced medications are large, complex proteins, many factors affect the quality of the end product, including glycosylation and presence of impurities, and thus many factors need to be compared between an emerging biosimilar and its originator biologic. Indeed, preclinical analytical assessments to determine similarity to an originator biologic are critical and are considered to be the foundation for regulatory approval of biosimilars. Here, the science behind the preclinical development of biosimilars is discussed by members of the International Psoriasis Council, and suggestions are put forth to try to ensure that future biosimilars are produced in a high quality and standardized manner. Abstract : What's known already about this topic? Biosimilars are biological drugs that are similar to an original marketed biological product. Approximately 40 different analytical methods are utilized to assess approximately 100 different drug attributes. Preclinical analytical assessments are used to determine similarity to an originator biologic and are critical for regulatory approval of biosimilars. What does this study add? The International Psoriasis Council suggests guidelines for standardization of preclinical assessments of emerging biosimilars through the development of a biosimilar index. Linked Comment: Villacorta, Br J Dermatol 2016; 174: 259–260 .